Hierarchical MoS2 Nanosheet@TiO2 Nanotube Array Composites with Enhanced Photocatalytic and Photocurrent Performances. Issue 11 (22nd January 2016) - Zheng, Lingxia; Han, Sancan; Liu, Hui; Yu, Pingping; Fang, Xiaosheng
Abstract : A novel type of hierarchical nanocomposites consisted of MoS2 nanosheet coating on the self‐ordered TiO2 nanotube arrays is successfully prepared by a facile combination of anodization and hydrothermal methods. The MoS2 nanosheets are uniformly decorated on the tube top surface and the intertubular voids with film appearance changing from brown to black color. Anatase TiO2 nanotube arrays (NTAs) with clean top surfaces and the appropriate amount of MoS2 precursors are key to the growth of perfect compositing TiO2 @MoS2 hybrids with significantly enhanced photocatalytic activity and photocurrent response. These results reveal that the strategy provides a flexible and straightforward route for design and preparation nanocomposites based on functional semiconducting nanostructures with 1D self‐ordered TiO2 NTAs, promising for new opportunities in energy/environment applications, including photocatalysts and other photovoltaic devices. Abstract : Novel TiO2 @MoS2 composites are successfully prepared by uniformly decorating hierarchical MoS2 nanosheets on both the top surface and the intertubular voids of 1D TiO2 nanotube arrays, which exhibit significantly enhanced photoactivity and improved photocurrent response. This flexible strategy is potentially applicable to design and optimize functional dual‐semiconductor material systems based on anodic self‐ordered TiO2 nanotube arrays.